Distingsi Stratifikasi Sosial Variasi Bahasa Sasak, Indonesia - Hasbullah; Muh Jaelani Al-Pansori (Lembaga Bale Literasi, 2022)
The purpose of this study was to determine the pattern of social stratification relations in the form of communication of the Sasak language variation. This type of research can be categorized as a qualitative descriptive research (post positive) because it is oriented towards finding values and influences, namely two focuses that have causality and a hierarchical relationship between social stratification and the existence of language. The research phase begins with problem identification, intensive observation, and then proceeds with the data acquisition stage. Data collection and acquisition techniques were carried out in three ways, namely interviews, observation, and documentation while the research data focused on two types of data, namely secondary data (written) through documents and empirical data (field) through observation and interviews. Determination of informants as sources are selected and determined by qualification and random based on certain criteria. After the data is obtained, the data will be analyzed using the method of data reduction and categorization. The results of this study conclude that: (1) stratification and social class in the Sasak community have a very large existence and influence in the mobility of the community. All aspects including language in the stratification and social class of the Sasak people will be formed differently into language classes (undak usuk) to show the criteria and identity of each group. (2) The forms of communication that occur in social society can be seen based on the context of the speakers who communicate with each other or with different groups, while in relation to social interaction, social interaction between groups will be high if their forms of communication are parallel (parallel) and social interaction will decrease if the form of communication is opposite and not comparable (diparallel).